Hematology, Morphology, Cytochemistry and Ultrastructure of Blood Cells in Painted Stork (Mycteria leucocephala) - Chaleow Salakij; Jarernsak Salakij; Nual-Anong Narkkong; Decha Pitakkingthong; Songkrod Poothong (Agriculture and Natural Resources, 2003)
Blood samples of 12 (7 males and 5 females) painted storks (Mycteria leucocephala), at the Bangpra Waterbird Breeding and Research Center, were collected from the cutaneus ulna vein for basic hematologic, light microscopic and transmission electron microscopic studies of blood cells. There was no hematozoa detected in all painted storks. There was no significant difference in all hematological values between the male and female groups. Lymphocytes were the most commonly observed leukocytes in the male painted storks and average 6-8 µm in diameter. Heterophils were the most commonly observed leukocytes in the females and were the second most commonly observed leukocytes in the males. Heterophils contained many pleomorphic, dull eosinophilic granules, ribosomes and lobed nucleus. Heterophils were the medium-sized cells, average 8-12 µm in diameter. Heterophils stained strongly positive with α-naphthyl acetate esterase (ANAE). Eosinophils revealed many small round granules and usually were the largest leukocytes, average 9-14 µm in diameter. The number of eosinophils was quite high in both the male and female painted storks. Eosinophil granules stained intensely with β–glucuronidase (β–glu), moderately to strong stained with ANAE and also stained with new methylene blue. Basophils were as small as lymphocytes but revealed many small granules surrounded central round nucleus. Basophils stained moderately with β–glu. Transmission electron microscopic examination revealed organelles within erythrocytes, heterophils, eosinophils and basophils.